Healthcare costs and resource utilization in patients with severe aplastic anemia in the US. (3rd October 2019) - Cai, Beilei; Said, Qayyim; Li, Xin; Li, Frank (Yunfeng); Arcona, Steve
Abstract: Purpose: This study aimed to evaluate the healthcare resource utilization (HCRU) and costs for patients with severe aplastic anemia (SAA) using US claims data. Methods: This retrospective, observational database study analyzed claims data from the Truven MarketScan databases. SAA patients aged ≥2 years identified between 2014 and 2017 who were continuously enrolled for 6 months before their first SAA treatment or blood transfusion, with a ≥6-month follow-up, were included. Baseline demographics and comorbidities were evaluated. Monthly all-cause and SAA-related HCRU and direct costs in the follow-up period were analyzed and differences were presented for all patients and across age groups. Results: With an average follow-up period of 21.5 months, 939 patients were included in the study. Monthly all-cause and SAA-related HCRU [mean (SD)] were 1.65 days (2.61 days) and 0.18 days (0.70 days) for length of stay, 0.18 (0.23) and 0.01 (0.04) for hospital admissions, 0.25 (0.30) and 0.02 (0.07) for ER visits, 2.24 (1.40) and 0.46 (0.99) for office visits, and 2.90 (2.64) and 0.55 (1.31) for outpatient visits, respectively. On average, SAA patients received 0.15 (0.57) blood transfusions per month. Mean monthly all-cause direct costs were $28, 280 USD ($36, 127) [US dollars, mean (SD)]. Direct costs related to admissions were $11, 433 USD (SD $25, 040), followed by $624 USD ($1, 703) for ER visits, $528 USD ($694) for office visits, $7, 615 USD ($13, 273) for outpatient visits, and $5, 998 USD ($11, 461) for pharmacy expenses. Monthly SAA-related direct costs averaged $7, 884 USD (SD $16, 254); of these costs, $1, 608 USD ($7, 774) were from admissions, $47 USD ($257) from ER visits, $127 USD ($374) from office visits, $1, 462 USD ($4, 994) from outpatient visits, and $4, 451 USD ($10, 552) from pharmacy expenses. Conclusion: SAA is associated with high economic burden, with costs comparable to blood malignancies, implying that US health plans should consider appropriately managing SAA while constraining the total healthcare costs when making formulary decisions.